EMPOWERING INDIAN BANKING THROUGH E-DELIVERY CHANNELS - Dr. R.K. Uppal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Transactions through e-channels cost much less to the banks than the customers reaching the bank and doing the transactions. In the post era of IT Act, expenditure on Information Technology in different bank groups is continuously increasing but new private sector banks and foreign banks are leader in challenges, this context. They are providing more facilities through ATMs (fixed ATMs, Mobile ATMs, ATMs in trains also), I-banking, Tele-banking etc and there is full computerization. The e-delivery channels are positively affecting the profitability of almost all the bank groups. ATM is the most popular e-channel in all the bank groups. The present paper analyses the correlation between the fully computerized branches as percentage of total branches with the profitability, similarly with other e-channels ratios like ATMs, I-banking, M-banking, Tele-banking) as percentage of total branches are correlated with bank groups profitability and ultimately, with the Indian banking industry. The present study is related to post information technology era. The paper highlights emerging issues, challenges and suggests some strategies and the future areas of intensive research. The paper also sparks on the future outlook of Information Technology in Indian banks.